2022
DOI: 10.12973/ijem.8.3.479
|View full text |Cite
|
Sign up to set email alerts
|

Observational Record and Self-Report of Teacher-Student Performance in High School Lessons

Abstract: <p style="text-align: justify;">There are different strategies to analyze teacher and student performance when they interact with each other in class. The most used strategies are direct observation and verbal reports. Even though what is observed or reported depends on theoretical frameworks regarding didactic interactions, these must be related to teacher functions such as supervision, providing feedback, and evaluation of student performance. In this study, instruments for observational recording and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Self-reports derived from this model of didactic performance have achieved stability and construct validity with restricted models of both teacher and student, and of various disciplines, contexts and educational levels [7,29,41]. Likewise, good goodness-of-fit has been found in predictive structural regression models with structural equation modeling.…”
Section: The Conceptual Framework Of This Studymentioning
confidence: 76%
See 4 more Smart Citations
“…Self-reports derived from this model of didactic performance have achieved stability and construct validity with restricted models of both teacher and student, and of various disciplines, contexts and educational levels [7,29,41]. Likewise, good goodness-of-fit has been found in predictive structural regression models with structural equation modeling.…”
Section: The Conceptual Framework Of This Studymentioning
confidence: 76%
“…For example, it has been reported that the effect of the transfer of digital competencies (information acquisition, communication, self-assessment, access to information, the application of digital security and problem solving), depends on the types of interaction with respect to the level or degree of studies and age groups [27]. On the other hand, discrepancies have been reported between the teacher's perception and the university student's perception of teacher performance and teaching quality [28,29], which are similar in the face-to-face context [7]. Additionally, a digital divide between faculty and students, low digital literacy, and inequality of access and connectivity have been reported [17,30].…”
Section: The Virtualization Of Teaching At the Level Of Higher Educat...mentioning
confidence: 99%
See 3 more Smart Citations